BURUH PEREMPUAN DI TENGAH KUBANGAN PARA KORUPTOR - Triana Sofiani (UIN K.H. Abdurrahman Wahid Pekalongan, 2012)
Abstract : The Center of hegemony, which is built on the common valuesÂ common interests between the rulers and capitalists who incidentally are in the sex of